Idiosyncrasies of biased investment choices in a culturally diverse context - Hayrapetyan, Davit; Heboyan, Arevik (Edelweiss Applied Science and Technology, 2025)
The purpose of this study is to determine the impact of personal and cognitive factors, decision making stylistic differences on investment decision making in various cultural settings, and their connections with cognitive biases and heuristics. A complex combination of psychological tests, financial tasks and self-assessment surveys was conducted among one hundred investors in the USA and seventeen investors Armenia to identify links between personality types and psychological characteristics of trading decision-making in multi-cultural study. This allowed us to visualize connections between personal factors (age, gender, education), decision-making styles, risk aversion and tolerance of ambiguity, financial literacy, and the impact of all these factors on biases we choose to utilize. Our results indicate that the knowledge and epistemic component function as a behavioral regulator, with financial literacy as a central determinant in investment patterns, determine tolerance towards uncertainty and risk aversion behavior. Gender and education, as well as investment stylistic factors determine the choice of biases. The lower number of participants from Armenia and stigma around investments and low trust in banks and financial market among Armenian investors is identifies as limitations for our study. This study is one of the first attempt to study and compare the distinctive features and peculiarities of Armenian investors and the factors determining their investing behavior.